Global financial transmission of monetary policy shocks - Michael Ehrmann; Marcel Fratzscher (Center for Economic Studies and ifo Institute (CESifo), 2006)
The paper shows that US monetary policy has been an important determinant of global equity markets. Analysing 50 equity markets worldwide, we find that returns fall on average around 3.8% in response to a 100 basis point tightening of US monetary policy, ranging from a zero response in some to a reaction of 10% or more in other countries, as well as significant crosssector heterogeneity. Distinguishing different transmission channels, we find that in particular the transmission via US and foreign short-term interest rates and the exchange rate play an important role. As to the determinants of the strength of transmission to individual countries, we test the relevance of their macroeconomic policies and the degree of real and financial integration, thus linking the strength of asset price transmission to underlying trade and asset holdings, and find that in particular the degree of global integration of countries - and not a country's bilateral integration with the United States - is a key determinant for the transmission process.
Keywords: F36; F30; G15; 330